A new population of the globally Endangered Red-fronted Macaw Ara rubrogenys unusually breeding in palms. Issue 3 (September 2014) - ROJAS, ABRAHAM; YUCRA, ELEUTERIO; VERA, IVÁN; REQUEJO, ANDRÉS; TELLA, JOSÉL.
Summary The Red-fronted Macaw Ara rubrogenys is endemic to Bolivia, where it is listed as "Critically Endangered" due to its reduced population size and persisting threats. This species is known to breed exclusively on steep cliffs in arid inter-Andean valleys. However, during a survey of the whole distribution, we noted a previously overlooked population breeding in stands of the also endemic and globally endangered palm Parajubaea torallyi. We observed five adult pairs and confirmed at least three active nests. Nests were in holes 14–20 m above the ground in dead palms, at 2, 580–2, 700 m asl. The scarcity of breeding habitat and current nest poaching were identified as the major threats for this population. This discovery broadens our understanding of the breeding ecology and widens the scope of action for the monitoring and conservation of the species.